2010
DOI: 10.1063/1.3289733
|View full text |Cite
|
Sign up to set email alerts
|

Electricity supply, irregularities, and the prospect for solar energy and energy sustainability in Sub-Saharan Africa

Abstract: Countries in Sub-Saharan Africa ͑SSA͒ are faced with the problem of expanding urban growth and demographic shift, necessitating the need to achieve a sustainable rate of positive economic growth. To move toward a sustainable future, many reforms have been implemented, including in the energy sector. Reforms in the energy sector will lead to a secure future energy supply, open globalised energy market, as well as providing basic energy needs. Unfortunately electrical energy production within SSA countries is pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…The exergy approach analysis of solar air-conditioning systems and their applicability was also reported by Koroneos et al [81]. Nkwetta et al [82] reported that considering the high temperature needed at the input of the generator of solar cooling systems, solar collectors designed for such applications will be cost effective if applied in combination for use with solar heating, sterilization unit and solar-powered absorption refrigeration system and proposed the schematic diagram in Fig. 11.…”
Section: Whole System Analysismentioning
confidence: 88%
See 1 more Smart Citation
“…The exergy approach analysis of solar air-conditioning systems and their applicability was also reported by Koroneos et al [81]. Nkwetta et al [82] reported that considering the high temperature needed at the input of the generator of solar cooling systems, solar collectors designed for such applications will be cost effective if applied in combination for use with solar heating, sterilization unit and solar-powered absorption refrigeration system and proposed the schematic diagram in Fig. 11.…”
Section: Whole System Analysismentioning
confidence: 88%
“…Nkwetta et al [82] further highlighted the need for this design to be use in running solar power air conditioning systems, sterilization of hospital equipment as well as for water treatment.…”
Section: Whole System Analysismentioning
confidence: 95%
“…Renewable resources has gained significant attention in recent years due to the cost increment and adverse environmental impacts of conventional fossil fuels [1]. Currently, Photovoltaic (PV)energy systems are considered as optimum solution to the electricity supply in most rural zones in developing countries [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…In rural regions, this could be achieved most economically by local decentralized installations, often working on renewable energy such as solar power, wind energy or biofuels [117,121].…”
Section: Policy Implicationsmentioning
confidence: 99%